A systematic approach to laparoscopic hysterectomy for enlarged uteri: The Ship Theory - Restaino, Stefano; Pellecchia, Giulia; Finelli, Angelo; Gioè, Alessandro; Arcieri, Martina; Cianci, Stefano; Paparcura, Federico; Poli, Alice; Uccella, Stefano; Scambia, Giovanni; Driul, Lorenza; Vizzielli, Giuseppe; et al. (Frontiers in Surgery, 2025)
Total laparoscopic hysterectomy (TLH) for enlarged uteri presents a significant challenge for surgeons due to limited surgical field exposure, increasing the risk of injury to the bowel, bladder, ureters, and blood vessels. To minimize these intraoperative complications, a surgical approach known as “The Ship Theory” has been developed at our center. According to this concept, the uterus is likened to a large vessel moored within the pelvis. As its supporting ligaments (“anchors”) are progressively released, the uterus gains mobility, allowing it to migrate into the abdominal cavity. This enhanced mobility improves visualization and facilitates surgical access, enabling a safer and more effective TLH for large uteri. Using this approach, we successfully performed this procedure on a 51-year-old female patient with uterine leiomyomas and metrorrhagia. Preoperative imaging revealed a uterus measuring 189 × 158 × 148 mm. Institutional review board and ethics committee approval was obtained. The total operative time was approximately 90 min, with an estimated blood loss of less than 50 mL. The patient was discharged 48 h postoperatively without complications. This technical report demonstrates that the application of a minimally invasive surgical technique for uteri with significant spatial constraints—as outlined in “The Ship Theory"—is not only feasible but can be successfully executed when performed in a systematic and structured manner.